Astragalus polyphenols attenuates doxorubicin-induced cardiotoxicity by activating the PI3K/AKT/NRF2 pathway - Xueyang Bai; Hua Wei; Gangqiong Liu; Ling Li (PLoS ONE, 2025)
Background Doxorubicin (DOX) is a powerful chemotherapeutic agent commonly employed in cancer treatment. However, its clinical utility is constrained by dose-dependent cardiotoxicity, which can result in heart failure and sudden cardiac death. The molecular mechanisms of DOX-induced cardiotoxicity (DIC) include oxidative stress, mitochondrial dysfunction, and the activation of cell death pathways, including ferroptosis. There is an urgent need for effective therapeutic strategies to mitigate DIC. Methods This study investigates the cardioprotective effects of Astragalus Polyphenols (ASP), a bioactive compound extracted from Astragalus membranaceus. In the context of DIC, we utilized AC16 and H9C2 cardiomyocytes to establish a DIC model and assessed the effects of ASP on cell viability, oxidative stress, mitochondrial function, and the PI3K/AKT/NRF2 signaling pathway. The expression of atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP), markers of cardiac injury, was also evaluated. Results ASP treatment significantly reversed DOX-induced reductions in cell viability and mitochondrial membrane potential (MMP) while also decreasing the levels of reactive oxygen species (ROS). Additionally, ASP also downregulated the expression of ANP and BNP, indicating a protective effect on cardiomyocytes. Furthermore, ASP activated the PI3K/AKT/NRF2 pathway, which was suppressed by DOX. Inhibition of this pathway using LY294002 and ML385 abolishes the protective effects of ASP, suggesting that ASP mediates its effects through the PI3K/AKT/NRF2 signaling axis. Conclusion ASP exhibits a protective effect against DOX-induced cardiotoxicity by regulating the PI3K/AKT/NRF2 pathway to reduce oxidative stress and preserve mitochondrial function. These findings suggest that ASP may serve as a potential therapeutic agent to alleviate DIC. Our results provide a novel strategy to protect the heart in patients undergoing DOX chemotherapy.